Next Stop, “Sunshine Station”: The Ontario Provincial Board of Health and the Exhibition of Tuberculosis, 1908-1929 - Murdock Smith, Jenna (Scientia Canadensis, 2011)
This article examines the Ontario Provincial Board of Health and its efforts to educate the public on disease and health through visual display. From 1908 to 1929, this government body put on various tuberculosis and public health exhibits that toured the province in a railway car and reached thousands of visitors annually at the Canadian National Exhibition. Throughout this period, officials went from putting an ad-hoc mix of materials on display to designing a sophisticated, dynamic exhibit that attracted thousands of visitors and was one of the most popular spaces on the CNE grounds. Drawing on the later work of Michel Foucault, I argue that the exhibition can be seen as a device of governmentality. Through this highly constructed space, the Board attempted to cultivate a reflexive and self-watching individual who would regulate his/her own behaviour according to certain hygienic standards and, in turn, demand the same conduct of others.